2020
DOI: 10.22207/jpam.14.2.24
|View full text |Cite
|
Sign up to set email alerts
|

Application of Plant Growth Promoting Bacillus thuringiensis as Biofertilizer on Abelmoschus esculentus Plants under Field Condition

Abstract: Plant growth promoting rhizobacterial strain Bacillus thuringiensis A5-BRSC was applied as charcoalbased biofertilizer on Abelmoschus esculentus plants under field condition for consecutive two years (spring-summer season). The objective of the present study is to evaluate the growth promoting parameters of the plant under field condition. Field application of biofertilizer showed statistically significant increase (at 0.05 levels by one-way ANOVA) in seed germination, shoot height, root length, leaf diameter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…It has been reported that Acinetobacter calcoaceticus displays IAA and siderophore production that promotes wheat plant growth, with antagonistic activity to different phytopathogens such as Fusarium oxysporum , Aspergillus flavus and A. niger ( Sarode Prashant et al, 2009 ). Bacillus thuringiensis isolate has also been reported to promote growth in Abelmoschus esculentus plants by phosphate solubilization ( Bandopadhyay, 2020 ). In our study, all five bacteria were capable of forming biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Acinetobacter calcoaceticus displays IAA and siderophore production that promotes wheat plant growth, with antagonistic activity to different phytopathogens such as Fusarium oxysporum , Aspergillus flavus and A. niger ( Sarode Prashant et al, 2009 ). Bacillus thuringiensis isolate has also been reported to promote growth in Abelmoschus esculentus plants by phosphate solubilization ( Bandopadhyay, 2020 ). In our study, all five bacteria were capable of forming biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most potential PGPR that can function as biofertilizers due to phytohormone production are Azospirillum (e.g., Coniglio et al, 2019) and Bacillus spp. (Kang et al, 2019;Bandopadhyay, 2020), and many others. Owing to the importance of phytostimulation, such PGPR are viable candidates for PGP as biofertilizers, especially if they can also solubilize plant nutrients and/or fix N to improve plant nutrition.…”
Section: Phytostimulatorsmentioning
confidence: 97%
“…To date few reports have been published about the successful use of Bt as a in field conditions 16,42,59,[82][83][84] . Sorokan et al, 2020 42 evaluate the efficiency of potatoes colonized with Bt in the control of L. decemlineata and potato viruses (Potato virus Y (PVY), Potato virus M (PVM), and Potato virus S (PVS)) in two different growth seasons.…”
Section: Effectiveness Of the Application Of Bacillus Thuringiensisor...mentioning
confidence: 99%